Regional Economic Outlook, May 2013, Western Hemisphere : Time to Rebuild Policy Space. (Regional Economic Outlook, 2013)
Despite some global risks, external conditions for Latin America should remain stimulative. With monetary policy in advanced economies expected to stay accommodative, external financing conditions will remain favorable. Strong demand from emerging Asian economies and the gradual recovery of advanced economies will continue to support commodity prices, benefiting exporters. The main policy challenge for most of the region is to take advantage of current conditions to continue buttressing a foundation for sustained growth. Other issues important to the region include: (i) strengthening balance sheets; (ii) understanding how changes in external conditions could impact public and external debt dynamics; and (iii) making the best use of the windfall from the recent terms-of-trade boom.